2018
DOI: 10.3389/fimmu.2018.01726
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Subsets: Phenotypes and Function in Tuberculosis Infection

Abstract: Monocytes are critical defense components that play an important role in the primary innate immune response. The heterogeneous nature of monocytes and their ability to differentiate into either monocyte-derived macrophages or monocyte-derived dendritic cells allows them to serve as a bridge between the innate and adaptive immune responses. Current studies of monocytes based on immunofluorescence, single-cell RNA sequencing and whole mass spectrometry finger printing reveals different classification systems for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
171
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(197 citation statements)
references
References 54 publications
13
171
0
1
Order By: Relevance
“…Gene expression profiles from TB patients and uninfected healthy controls have been reported by several groups in the past to provide new knowledge on the immune response that takes place during active TB (19). In comparison, tissue samples from extrapulmonary TB have been poorly studied (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiles from TB patients and uninfected healthy controls have been reported by several groups in the past to provide new knowledge on the immune response that takes place during active TB (19). In comparison, tissue samples from extrapulmonary TB have been poorly studied (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, inflammatory monocytes can also play a deleterious effect by fueling and perpetuating the inflammatory response leading to unrestricted control of microbial infection and tissue pathology (Shi and Pamer, 2011;Pahari et al, 2018;Sampath et al, 2018). Our group and others have reported phenotypic and functional alterations in monocytes from TB patients compared to healthy controls (Sanchez et al, 2006;Balboa et al, 2011;Castaño et al, 2011a,b;Lastrucci et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
“…The transcriptome of human monocytes and monocyte subsets has been examined under different circumstances, mostly from healthy control individuals (MoCT) (Martinez et al, 2006;Ancuta et al, 2009;Fairfax et al, 2014;Rinchai et al, 2016;Kapellos et al, 2019). However, much less information exists concerning the transcriptome of human monocytes from TB patients (MoTB) (Esterhuyse et al, 2015;Sampath et al, 2018), and no actual information has been reported on the consequences of Mtb infection of circulating MoTB based on the potential consequences of monocytes infection at the sites of infection. Using genome-wide global gene expression, we first investigated transcriptional responses of circulating MoTB, aiming to understand the systemic effect of the disease on its gene expression profile.…”
Section: Introductionmentioning
confidence: 99%
“…Within human blood, there exists three distinct subpopulations of monocytes based on their cell surface markers (mainly the presence of CD14 and CD16) and functionality. CD14 + /CD16 − monocytes, also known as classical monocytes, are functionally antimicrobial and highly pro‐inflammatory whereas CD14 + /CD16 ++ monocytes, known as nonclassical monocytes, are functionally anti‐inflammatory (Sampath, Moideen, Ranganathan, & Bethunaickan, ). Studies on monocytes in TB found that nonclassical monocytes (CD14 + /CD16 ++ ) expanded with TB progression, whereas anti‐TB treatment reversed this expansion (Castaño, GarcĂ­a, & Rojas, ; SĂĄnchez et al, ).…”
Section: Tb Pathophysiology and The Role Of The Immune Systemmentioning
confidence: 99%
“…This would certainly be expected to boost immune defence against TB infection. In addition, classical monocytes exhibit up‐regulated myeloperoxidase (MPO) expression (Sampath et al, ), which is usually abundant in neutrophils. A recent study revealed that MPO can metabolize INH to form an INH‐NAD + adduct; the latter is considered an active metabolite of INH, which inhibits the cell wall synthesis of Mtb (Khan et al, ).…”
Section: Tb Pathophysiology and The Role Of The Immune Systemmentioning
confidence: 99%